Magnetic field dependence of electrical resistivity and thermopower in Ni50Mn37Sn13 ribbons - Maheswar Repaka, Durga Venkata (2015)
We report magnetization, magnetoresistance (MR) and magnetothermopower (MTEP) of melt spun Ni 50Mn37Sn13 ribbons which exhibit an austentite to martensite phase transition at a temperature (TM ) ≈ 294 K. Upon cooling from 400 K, dc-resistivity and thermopower show abrupt changes at TM , indicating a change in the electronic density of states. The thermopower is negative from 400 K down to 10 K. Application of a magnetic field of μ 0 H = 5 T decreases TM by 5 K and induces large negative MR (-23%) but positive MTEP (9%) near TM . While the MR is appreciable from TM down to 10 K, MTEP is significant only below 60 K (MR = -2.5% and MTEP = +300% at 10 K). The magnetic field dependence of resistivity and thermopower show either reversible or irreversible behavior near TM , depending on whether the sample is zero-field cooled or field-cooled, which indicates that the electronic band structure near TM is magnetic history dependent.